Role of attitude and intention on the relationship between perceived ease of use, perceived usefulness, trust, and e-tax system behavior - Hikmah; Andalan Tri Ratnawati; Susetyo Darmanto (Global Business & Finance Review (GBFR), 2023)
Purpose: The study proposes to analyze the effect of perceived ease of use on perceived usefulness and trust. Furthermore, the s tudy examined the mediation effect of attitude and intention on behavior to use the e-tax system. Design/methodology/approach: This study uses a quantitative approach with a survey as a data collection method. Respondents are 150 small and medium entrepreneurs in Central Java, Indonesia, who have used e-tax system. Findings: The results showed that perceived ease of use positively affects perceived usefulness and trust. Other results demonstrated that perceived ease of use, perceived usefulness, and trust have positive contributions toward attitude. Furthermore, the study confirmed that attitude has a significant influence on intention, however, trust has no effect. Finally, the finding reveal that intention predicted e-tax system behavior. Research limitations/implications: The results reveal that perceived ease has a significant influence of perceived usefulness and trust. Therefore, perceived ease of use, perceived usefulness, and trust are significant determinants of tax attitude, intention, and behavior to use the e-tax system. Originality/value: The study contributes to TAM theory by adding the sociodemographic characteristics of SME entrepreneurs on the e-tax system behavior, and the mediating role of attitudes and intentions in the relationship between factors of tax behavior.
Keywords: 650; perceived ease of use; perceived usefulness; trust; attitude; intention; behavior to use the e-tax system